2006
DOI: 10.1074/jbc.m600912200
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Pathway for Dystroglycan Function in Acetylcholine Receptor Aggregation and Laminin Deposition in Skeletal Myotubes

Abstract: The dystroglycan (DG) complex is involved in agrin-induced acetylcholine receptor clustering downstream of muscle-specific kinase where it regulates the stability of acetylcholine receptor aggregates as well as assembly of the synaptic basement membrane. We have previously proposed that this entails coordinate extracellular and intracellular interactions of its two subunits, ␣-and ␤-DG. To assess the contribution of the extracellular and intracellular portions of DG, we have used adenoviruses to express full-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 90 publications
4
18
0
Order By: Relevance
“…4D; Table 1), indicating that, as discussed earlier, the Dg extracellular domain alone might function in some capacity to regulate egg chamber growth. This is similar to what is seen with skeletal myotubes (39). DC2 and 4P, however, rescued egg chamber growth at the same level as the FL (Fig.…”
Section: The Region Of the Dystroglycan C Terminus Containing Wwbsii supporting
confidence: 72%
See 1 more Smart Citation
“…4D; Table 1), indicating that, as discussed earlier, the Dg extracellular domain alone might function in some capacity to regulate egg chamber growth. This is similar to what is seen with skeletal myotubes (39). DC2 and 4P, however, rescued egg chamber growth at the same level as the FL (Fig.…”
Section: The Region Of the Dystroglycan C Terminus Containing Wwbsii supporting
confidence: 72%
“…Nevertheless, in all the assays described, some phenotypes above the control level were observed even with the constructs that lack most of the C-terminal domain (C1; Fig. 3, F-H), indicating that the Dg extracellular domain alone might function in some capacity to regulate cellular polarity (similar to seen in other systems (30,39).…”
Section: The Region Of the Dystroglycan C Terminus Containing Wwbsii mentioning
confidence: 97%
“…6). These findings are not surprising in view of recent evidence suggesting that b-DG might have independent functions in organizing cell surface proteins (Kahl and Campanelli, 2003;Driss et al, 2006;Tremblay and Carbonetto, 2006). Thus, an increased expression level of b-DG subunit might be per se able to promote, directly and/or indirectly (i.e., stabilizing other adhesion molecules), cell adhesion.…”
Section: Discussionmentioning
confidence: 62%
“…The dystrophin-associated glycoprotein complex (DGC), which links the myofiber cytoskeleton to the basal lamina through the sarcolemma, is also assembled in vitro. DGC components, including dystrophin (Chal et al, 2015;Ozasa et al, 2007), dystroglycan and integrins (Hirsch et al, 1998;Jacobson et al, 2001;Tremblay and Carbonetto, 2006), were found distributed at the sarcolemma of PSC-derived myofibers (Fig. 5, Tables S1 and S2).…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 99%
“…Patch clamp and gene expression analyses of mESC-derived myotubes have shown that this developmental transition can also occur in vitro, as these cells start to express the adult AchRε after 2 weeks of differentiation (Guan et al, 1999;Jacobson et al, 2001;Rohwedel et al, 1998bRohwedel et al, , 1994Tremblay and Carbonetto, 2006) (Fig. 5B).…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%